(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
To investigate the compressive effects through microscopic features of flexible low-density open-cell PU foam during moulding process, FE simulation of deformation based on a regular dodecahedron cell unit with uniaxial compression behavior is undertaken to examine the mechanical properties of the vertical loading direction, and to facilitate the incorporation of solid PU material properties and variations in cell geometry. By the use of a factorial design, the mean strut thickness of solid struts has a positive non-linear effect on the maximum reaction force as compared against cell size with a negative non-linear effect. The Young's modulus of solid polymers had a positive linear effect on the response while the Poisson's ratio had the least impact on the response. Development of a simplified cell unit can model the behavior of open-cell PU foam under uniaxial compression which is an effective way to understand the mechanical behavior of foam during moulding process.